The Effectiveness Of Plastic Formworks In Construction - Lam, Jam Isnain (Universiti Sains Malaysia, 2005)
A new construction method replacing rigid formwork panels with flexible textile membrane that deflects under the dead weight of wet concrete, provide numerous advantages and opportunities for architecture, engineering, and construction technology in both advanced and basic building economies. Inexpensive formwork fabrics provide the options of sacrificial or reusable formworks in both precast and cast-in-place applications. A method has been developed for fabric-cast foundation, walls, columns, capitals, slab, and beam. Permeable membranes allow air bubbles and excess mix water to bleed out, producing a flawless, cement-rich finish and stronger and more durable “case hardened” concrete. Structurally efficient variable section members are easily formed, reducing dead weight and material expenses. Most formwork panels these days are faced with plywood. Plywood is sensitive to moisture and can swell, warp and discolour the concrete surface. Plywood is difficult to clean, is easily damaged in use, and can only be repaired at some expense and not without visible traces. For several years now, formwork panels with plastic surface – mainly made of polypropylene (PP) – have also been available on the market. Although these overcome the problems associated with plywood, they are very sensitive to scratching and in many cases, after only relatively few uses, are unable to guarantee a smooth concrete surface.